2013
DOI: 10.1021/nn404845q
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Subsurface of Soft Matter: Simultaneous Topographical Imaging, Depth Modulation, and Compositional Mapping with Triple Frequency Atomic Force Microscopy

Abstract: Characterization of subsurface morphology and mechanical properties with nanoscale resolution and depth control is of significant interest in soft matter fields like biology, polymer science, and even in future applications like nanomanufacturing, where buried structural and compositional features are important to the functionality of the system. However, controllably "feeling" the subsurface is a challenging task for which the available imaging tools are relatively limited. In this paper, we propose a trimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
135
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 49 publications
6
135
0
Order By: Relevance
“…22 In particular, Ebeling et al have been able 3 to image glass nanoparticles (NPs) embedded in a soft Polydimethylsiloxane (PDMS) film. 23 UFM has specifically proven a valid tool to localize subsurface defects in stiff materials.…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, Ebeling et al have been able 3 to image glass nanoparticles (NPs) embedded in a soft Polydimethylsiloxane (PDMS) film. 23 UFM has specifically proven a valid tool to localize subsurface defects in stiff materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has several configurations depending on the feedback schemes [16][17][18][19][20][21][22][23][24]. In the first bimodal AFM configuration (bimodal AM) [15,16], the feedback acts on the amplitude of the first mode by keeping it at a fixed value during imaging while the second mode operates in an open loop.…”
Section: Introductionmentioning
confidence: 99%
“…2 The higher harmonics are generated by the tip-sample interactions, which can be used to extract information on the material properties. [3][4][5][6][7][8][9][10] The enhanced resolution, 6,9 sensitivity 7 and better contrast 10,11 can be obtained in higher harmonics. For example, García et al 9 demonstrated that bimodal AFM enables fast, accurate and angstrom-scale Young's modulus mapping on a wide range of materials in air and liquid.…”
mentioning
confidence: 97%
“…The trimodal AFM can be used as separate control "knobs" to simultaneously measure the topography, map compositional contrast and modulate sample indentation by the tip during tip-sample impact, respectively. 10 However, the higher harmonic signals are suppressed due to the rapid decay of frequency response curve of the uniform cantilever, 12 which may result in a small signal output that is even lower than the effective noise level. The vibration amplitudes of the higher harmonics are several orders of magnitude smaller than that of the fundamental component.…”
mentioning
confidence: 99%
See 1 more Smart Citation